Model biznesowy dyrygenta w warunkach kompresji czasu - opis przypadku - Drzewiecki, Jakub (The conductor business model under time compression diseconomies circumstances - case description, 2006)
The goal of the paper is to describe an example of effective conductor business model application under time compression diseconomies circumstances. In the paper, an example of a company which applied this type of business model and succeeded in many areas, was described. Therefore, the conductor business model may be a good way to cope with time compression diseconomies connected with the need of quick and effective obtaining various resources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 556-563